A semiótica e a construção de uma educação musical crítica - Piva, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The aim of the present work is to understand the possible connections between semiotics and music education, surrounding the issues that involve the understanding of music as a language and seeking a political and critical music education. For this purpose, answers are sought in Charles Sanders Peirce's semiotic theory, in order to define the concepts of sign, object and interpretant and the functioning of the trichotomies arising from the relationships between these elements. Three theories of musical semiotics, based on Peirce, are chosen to understand their possible applications in musical language. Semiotics is a developing field and the study of its applications in music deserves to be further explored. The work is also based on Paulo Freire's thought to elucidate the discussion about education and society, considering the political-ideological complexity of the pedagogical act. From the articulation between semiotics and music education, reflections were raised on the importance of music educators reviewing their own conceptions about musical language, the role of music education in society and how these matters impact their pedagogical practice.

O presente trabalho tem como objetivo compreender as possíveis pontes entre semiótica e educação musical, permeando as questões que envolvem o entendimento da música enquanto linguagem e visando uma educação musical política e crítica. Para tal fim, busca na teoria semiótica de Charles Sanders Peirce a definição dos conceitos de signo, de objeto e de interpretante e o funcionamento das tricotomias decorrentes das relações entre esses elementos. São eleitas três teorias de semiótica musical, fundamentadas em Peirce, para entender as suas possíveis aplicações na linguagem musical. A semiótica é um campo em desenvolvimento e o estudo de suas aplicações no âmbito da música merece ser mais explorado. O trabalho fundamenta-se, também, no pensamento de Paulo Freire para elucidar a discussão acerca de educação e sociedade, considerando a complexidade político-ideológica do ato pedagógico. A partir da articulação entre semiótica e educação musical, foram levantadas reflexões sobre a importância do educador musical revisar suas próprias concepções acerca da linguagem musical, do papel da educação musical na sociedade e como estas questões impactam a sua prática pedagógica.
Semiotics and the construction of a critical music education
Keywords: Semiótica; Educação musical; Pedagogia crítica